2019
DOI: 10.1093/biolre/ioz085
|View full text |Cite
|
Sign up to set email alerts
|

Follicle-stimulating hormone and luteinizing hormone increase Ca2+ in the granulosa cells of mouse ovarian follicles†

Abstract: In mammalian ovarian follicles, follicle stimulating hormone (FSH) and luteinizing hormone (LH) signal primarily through the G-protein Gs to elevate cAMP, but both of these hormones can also elevate Ca2+ under some conditions. Here, we investigate FSH- and LH-induced Ca2+ signaling in intact follicles of mice expressing genetically encoded Ca2+ sensors, Twitch-2B and GCaMP6s. At a physiological concentration (1 nM), FSH elevates Ca2+ within the granulosa cells of preantral and antral follicles. The Ca2+ rise b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…31,32 The expression of these enzymes converts androstenedione synthesized from follicular theca cells into E2. Although studies have reported that FSH affects the development of preantral follicles, [33][34][35] there is no report regarding the effect of FSH on the growth pattern of preantral follicles in vitro. The reason may be that the PM follicles and ES follicles were cultured together in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31,32 The expression of these enzymes converts androstenedione synthesized from follicular theca cells into E2. Although studies have reported that FSH affects the development of preantral follicles, [33][34][35] there is no report regarding the effect of FSH on the growth pattern of preantral follicles in vitro. The reason may be that the PM follicles and ES follicles were cultured together in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…In 10 mIU/mL r‐FSH culture medium, ES follicles exhibited a tiled growth pattern, with large adherence area; while in 100 mIU/mL r‐FSH culture medium, they presented a three‐dimensional growth pattern, with small adherence area. Although studies have reported that FSH affects the development of preantral follicles, 33‐35 there is no report regarding the effect of FSH on the growth pattern of preantral follicles in vitro. The reason may be that the PM follicles and ES follicles were cultured together in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our outcomes here may reflect our core facility capabilities as much as inherent limitations in consistent Cas9 mediated oocyte targeting of large constructs. The successful outcomes here and in a prior publication demonstrate the use of the system to develop lines capable of functional imaging (62).…”
Section: Discussionmentioning
confidence: 71%
“…10 B). The data demonstrate how the targeting system here can be used to build conditional mouse lines that are useful beyond the nervous system and throughout the body (62).…”
Section: Select Mouse Line Characterizationmentioning
confidence: 87%
“…This fate mapping effect can be circumvented by induction of GECI expression after neuronal and oligodendroglial maturation in inducible Cre driver mouse lines (tamoxifen or tetracycline/doxycycline). For some GECIs, transgenic mouse lines to allow for glia-specific Ca 2+ imaging have been published, but are not commercially available (Yoshikawa et al, 2016;Egbert et al, 2019). According to our knowledge, we indicate whether transgenic mice, rAAVs, or plasmids ready-to-use for astrocytic expression are available and listed those in Supplementary Table 1.…”
Section: Glia-specific Expression Of Gecismentioning
confidence: 99%